Theories of Leadership and Church Management - Joseph Tong (Sekolah Tinggi Teologi Excelsius, 2019)
Management is the integration and coordination of resources to effectively move the organization towards the desired goals. The concepts and key elements in management are organizations. This organization is also divided into two namely: voluntary organizations and voluntary organizations. The objectives of this management are: (1) Vision and mission for existence; (2) Objectives and targets; (3) The desired destination and floating destination. Management effectiveness refers to how well an organization reaches its goals over a period of time. This emphasizes goals or mission (long distance) and goals (short term). Effectiveness contrasts with efficiency. Efficiency is a short-term measure of how well an organization uses resources. Healthy organization management must be effective and efficient. Leadership relates to people, while management pays more attention to tasks and performance. As far as the organization is concerned, these two things have the same function in promoting the well-being and development of healthy organizations to achieve organizational goals. Manajemen adalah integrasi dan koordinasi sumber daya untuk menggerakkan organisasi secara efektif menuju tujuan yang diinginkan. Adapun konsep dan elemen kunci dalam manajemen yaitu organisasi. Organisasi ini pun dibagi menjadi dua yakni: organisasi sukarela dan organisasi tidak sukarela. Tujuan dari manajemen ini adalah: (1) Visi dan misi untuk eksistensi; (2) Tujuan dan target; (3) Tujuan yang diinginkan dan tujuan mengambang. Efektivitas manajemen mengacu pada seberapa baik sebuah organisasi untuk mencapai tujuannya selama periode waktu tertentu. Hal ini menekankan pada tujuan atau misi (jarak jauh) dan tujuan (jangka pendek). Efektivitas kontras dengan efisiensi. Efisiensi adalah ukuran jangka pendek seberapa baik sebuah organisasi menggunakan sumber daya. Manajemen organisasi yang sehat harus efektif dan efisien. Kepemimpinan berkaitan dengan orang, sedangkan manajemen lebih memperhatikan tugas dan kinerjanya. Sejauh menyangkut organisasi, dua hal ini memiliki fungsi yang sama dalam mempromosikan kesejahteraan dan pengambangan organisasi yang sehat untuk mencapai tujuan organisasi.